Live weight gain in the rearing and reproductive performance of yearling beef heifers mated - Montanholi, Yuri Regis; Barcellos, Júlio Otávio Jardim; Borges, João Batista; Costa, Eduardo Castro da; Wunsh, Carolina; Prates, Ênio Rosa (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the effects of growth rate during rearing period, from 13 to 18 months, on pregnancy rate of beef heifers mated at yearling during autumn. Treatments consisted of 30 heifers weighing on average 208 kg submitted to average growth rate of 0.595 kg day-1 (G600), 41 heifers averaging 197 kg with average growth rate of 0.656 kg day-1 (G700) and 58 heifers with 181 kg with average growth rate of 0.723 kg day-1 (G800). Treatment effects were determined on body weight, reproductive tract score and pregnancy rate. Pregnancy rate was 30.0% 47.8% and 50.0%, respectively, for G600, G700 and G800, without significant differences among groups. Treatments G700 and G800, with large growth rates, showed higher values of reproductive tract score than G600 at the start of the mating period. Heifers with higher scores had a tendency to present higher pregnancy rates. Pregnancy rates were related to growth rate during postweaning independently of weight variations at mating.